Physiological response to excessive doses of indolyl-3-butyric acid and its potassium salt in stimulating the rooting of semi-woody cuttings of coniferous crops - Borovkov V.V.; Demchenko G.A. (BIO Web of Conferences)
The study of root formation stimulation in cuttings of coniferous crops is often accompanied by a decrease in survival rate with an increase in the content of indolyl-3-butyric acid or its potassium salt in the regulator above a certain value. In contrast to cases of hormone deficiency in the stimulant, when cuttings remain alive, but root formation does not occur or a callus is formed, with excessive concentrations, the death of cuttings is observed. Under the conditions of film cutting tunnels equipped with substrate heating, observations were made on the condition of cuttings of coniferous crops in variants with an increasing concentration of exogenous auxin, leading to a decrease in survival rate. It is shown that in such variants, the appearance of cuttings with a “rotten base” is observed, which are a transitional form between healthy well-rooted cuttings and completely dead ones.